A Cross-Sectional Study of Labor Analgesia Practices Across India - Kajal Jain; Nidhi Bhatia; Ketan Parikh; Karan Singla; Ankita Dhir; Sunanda Gupta; Anju Grewal; Anjan Trikha (Wolters Kluwer Medknow Publications, 2024)
Introduction: Labour analgesia practices have evolved significantly over the past years, with most of the current practices being evidence-based. Labour analgesia is considered a standard of care in resource-rich countries. However, in resource-limited countries such as India, there is a lack of awareness, and round the clock availability of labour analgesia services across the country. This raises significant challenges in establishing successful labour analgesia programs. Methods: This survey was conducted using multi-question Google Form@, so as to improve our understanding of labour analgesia practices in India. Our primary objective was to study the prevalence of labour analgesia practices amongst anaesthesiologists across India. Our secondary objectives included the work profile of anaesthesiologists providing labour analgesia, common techniques of labour analgesia practised, drugs used and common complications as well as side-effects encountered. Results: The results of our survey showed that 72.9% of the respondents practised labour analgesia in one form or the other. Practitioners in non-government facilities such as private hospitals, private medical colleges, and nursing homes accounted for more than 60% of the total labour analgesia delivered. Government medical colleges fared the best among practitioners at government-owned facilities. Approximately 85% of those polled agreed that the most common way of pain relief in a labouring patient was regional analgesia. The most prevalent was labour epidural (59.4%), followed by a single shot spinal analgesic, while 29% of anaesthesiologists used systemic analgesia. Conclusion: The impediments to delivering widespread labour analgesia services across India were poor infrastructure and high costs.